2019
DOI: 10.36251/josi.163
|View full text |Cite
|
Sign up to set email alerts
|

Music education as a means to enhance the perceived sense of social inclusion and to empower the young through increased employment in Eastern Uganda

Abstract: Uganda has a rich culture in music, with musical skills having traditionally been passed down orally from one generation to the next. In school, music as a subject is featured in the National Curriculum; however, its teaching varies widely from school to school. Yet, due to music playing a vital role in the culture, musical activities take place daily and musicians are regularly needed in events. Engaging in musical activities could potentially empower young Ugandans and help them with feeling socially include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…I found seven studies that discuss community‐based or government initiatives, which have aimed to enhance the social inclusion of marginalised peoples through music education (Jeanneret & Brown, 2012; Junqueira, 2010; Sauer, 2012; Tettey, 2019; Welch et al, 2014; Yerichuk, 2015; Yerichuk & Krar, 2019). For example, Welch et al (2014) examined, through a research evaluation, if there is a link between children's singing development and their feelings of social inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…I found seven studies that discuss community‐based or government initiatives, which have aimed to enhance the social inclusion of marginalised peoples through music education (Jeanneret & Brown, 2012; Junqueira, 2010; Sauer, 2012; Tettey, 2019; Welch et al, 2014; Yerichuk, 2015; Yerichuk & Krar, 2019). For example, Welch et al (2014) examined, through a research evaluation, if there is a link between children's singing development and their feelings of social inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are personal and environmental level social exclusion factors, such as ill health, limited income, social stigma, and transportation difficulties, young people are resilient, creative, and innovative enough to identify and take advantage of opportunities for social inclusion. Formal and informal networks that afford and support access to different identities and resources (Brady et al, 2020; Kermode et al, 2021; Korkiamaki & O’Dare, 2021; Tettey, 2019) are means by which young people participate in activities that promote personal growth and community building. The findings suggests that, to some extent, young people in NL derive the benefits of social inclusion, including the development of personal and interpersonal skills (Korkiamaki & O’Dare, 2021; Olsson et al, 2018; Rose et al, 2012), to help navigate the transition to adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that support for youth entrepreneurship is a great way to empower young people to pursue careers in the informal economy and to contribute to building their communities. In addition, research by Tettey (2019) has shown that engaging youth in culturally grounded activities such as music and dance enables young people to develop artistic talents and stay connected to their communities. Further, research has found that formal interventions targeted to youth, such as peer-led wellness groups, do well to in promoting a sense of social inclusion among youth who are mentally ill by reducing social isolation (Kermode et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation